Response to Kanellis: - Maria-Rosa Watson, DDS, MS, MPH (2000)
Dr. Kanellis has prepared a comprehensive overview of the strategies for idenbfying children at high risk for dental decay and the scientifically proven approaches for preventing tooth decay in these children (1). The following comments are meant to encourage further thought, discussion, and possibly provide some encouragement for the implementation of innovative approaches that have not been fully explored in the dental field.